Left anterior descending artery hyper dominance giving rise to the posterior descending artery: an extremely rare coronary anomaly and its clinical implications - Muhammad Shabbir Rawala; Alex Munoz; S. Tahira Shah Naqvi; Mohammad Hassan Pervaiz (Journal of Community Hospital Internal Medicine Perspectives, 2020)
The prevalence of congenital coronary artery anomalies is approximately 1% in the general population. They are a common cause of sudden death in younger persons. The origination of the posterior descending artery (PDA) from left anterior descending (LAD) artery is an extremely rare anomaly. We present a case of a 54-year-old female who presented with diabetic ketoacidosis with co-existing non-ST elevation myocardial infarction, therefore, had an invasive angiogram that identified the anomalous origin of PDA from LAD. It is vital to define coronary anatomy as anomalies dictate which cardiac intervention should be attempted in cases of ischemia.